Design and Performance Evaluation of Hybrid Solar-Thermal and Biomass Dryer Systems for Post-Harvest Agricultural Products - Terttiaavini Terttiaavini; Asmawati Asmawati; Normah Normah (Green Engineering: International Journal of Engineering and Applied Science, 2024)
This study investigates the performance and sustainability of a hybrid solar-biomass drying system for agricultural products, focusing on its efficiency, environmental impact, and economic feasibility. The hybrid system combines solar energy and biomass combustion to create a continuous and reliable drying process. The key findings reveal that the hybrid system achieves over a 20% improvement in drying efficiency compared to solar-only and biomass-only dryers. This efficiency gain is attributed to the synergistic use of solar energy during the day and biomass energy during periods of low sunlight or at night, ensuring consistent drying conditions and reduced drying time. Additionally, the hybrid system significantly reduces CO₂ emissions, contributing to a more sustainable approach to agricultural processing. The environmental benefits of using renewable energy sources, as opposed to fossil fuels, align with the growing need for energy-efficient and eco-friendly agricultural technologies. Economic analysis suggests that the hybrid system is a cost-effective solution for small- to medium-scale farmers, particularly in rural areas where access to grid electricity is limited. The use of locally available biomass fuels further enhances the system’s sustainability and affordability. This study also discusses the practicality of implementing hybrid dryers in rural farming communities, emphasizing their potential to improve drying efficiency, reduce environmental impacts, and boost economic opportunities for farmers. Future research should focus on optimizing system integration, expanding biomass fuel options, and exploring automation to enhance the performance and scalability of hybrid drying systems.